Advanced characterizations of nanoparticles for drug delivery: Investigating their existence through the techniques used in their evaluations - Mahmood, Sayed; Chatterjee, Bappaditya; Mandal, Uttam Kumar (Walter de Gruyter GmbH, 2016)
Nanomedicine has achieved a huge success in delivering a wide variety of drug molecules into the target site of the body. In this respect characterization of nano formulation is very important to investigate the drug molecule together with its carrier as a nano form during formulation, storage and in vivo transport through the body. This review article summarizes important advanced characterization techniques of nano formulation with respect to their theories, the use of required instrumental parameters, sample preparation techniques, data interpretation, etc. in order to exploit them for the best possible results. This review article also sheds a glimpse to the shortcomings of these techniques together with further advancements required in future.